Revision of the sponge genus Pleroma Sollas (Lithistida: Megamorina: Pleromidae) from New Zealand and New Caledonia, and description of a new species - Michelle Kelly (New Zealand Journal of Marine and Freshwater Research, 2003)
Diagnostic morphological characters for the sponge genus Pleroma , relicts from a diverse group of lithistid sponges (Suborder Megamorina: Family Pleromidae) that were once common in the north‐western European late Jurassic to the late Cretaceous (c. 140–65 Ma), are reviewed following examination of new collections of known species from northern New Zealand and the south New Caledonian slope. Before this work, only two living species of Pleroma were known, the genus holotype P. turbinatum Sollas from Fiji, and P. menoui Lévi & Lévi from south New Caledonian seamounts. A new species, P. aotea n. sp., is described from northern New Zealand waters, extending the suite of diagnostic characters to include nodulose megaclone desmas and amphiaster microscleres. Megaclone desmas, indistinguishable from those of P. menoui and P. aotea n. sp., are recorded from the Oamaru Diatomite in southern New Zealand (late Eocene), and the Tutuiri Greensand, Chatham Island (late Palaeocene), respectively. These published and new microfossil discoveries establish a disjunct geographic distribution for Pleroma in New Zealand.